Recent trends in antipsychotic polypharmacy in the treatment of schizophrenia - Norio Yasui‐Furukori; Kazutaka Shimoda (Wiley, 2020)
Abstract Ichihashi et al reported that 43% of patients had antipsychotic polypharmacy. Number of antipsychotics used in patients with schizophrenia in Japan was the greatest among Asian countries. However, the antipsychotic polypharmacy rate in Japan decreased gradually. Recent systematic review, meta‐analysis and meta‐regression analysis demonstrated that antipsychotic augmentation was superior to monotherapy. However, several cohort studies have suggested a significant association between antipsychotic daily dose and mortality. In addition, most pharmacokinetic interactions with antipsychotics occur at the metabolic level and usually involve changes in the activity of the major drug‐metabolizing enzymes involved in their biotransformation. Thus, avoidance of unnecessary polypharmacy, knowledge of the interaction profiles of individual agents, and careful individualization of dosage based on close evaluation of clinical response and possibly plasma drug concentrations are essential to prevent and minimize potentially adverse drug interactions in patients receiving antipsychotics.